SARS-CoV-2 seroprevalence among the general population and healthcare workers in India, December 2020–January 2021. (July 2021) - Murhekar, Manoj V.; Bhatnagar, Tarun; Thangaraj, Jeromie Wesley Vivian; Saravanakumar, V.; Kumar, Muthusamy Santhosh; Selvaraju, Sriram; Rade, Kiran; Kumar, C.P. Girish; Sabarinathan, R.; Turuk, Alka; Asthana, Smita; Balachandar, Rakesh; et al.
Highlights: By December 2020, 24.1% of the general population in India had been exposed to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). For every case of coronavirus disease 2019 detected, there were 27 infections. Seroprevalence was higher in urban areas compared with rural areas. By December 2020, 25.6% healthcare workers had evidence of SARS-CoV-2 infection. Abstract: Background: Earlier serosurveys in India revealed seroprevalence of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) of 0.73% in May–June 2020 and 7.1% in August–September 2020. A third serosurvey was conducted between December 2020 and January 2021 to estimate the seroprevalence of SARS-CoV-2 infection among the general population and healthcare workers (HCWs) in India. Methods: The third serosurvey was conducted in the same 70 districts as the first and second serosurveys. For each district, at least 400 individuals aged ≥10 years from the general population and 100 HCWs from subdistrict-level health facilities were enrolled. Serum samples from the general population were tested for the presence of immunoglobulin G (IgG) antibodies against the nucleocapsid (N) and spike (S1-RBD) proteins of SARS-CoV-2, whereas serum samples from HCWs were tested for anti-S1-RBD. Weighted seroprevalence adjusted for assay characteristics was estimated. Results: Of the 28, 598 serum samples from the general population, 4585 (16%) had IgG antibodies against the N protein, 6647 (23.2%) had IgG antibodies against the S1-RBD protein, and 7436 (26%) had IgG antibodies against either the N protein or the S1-RBD protein. Weighted and assay-characteristic-adjusted seroprevalence against either of the antibodies was 24.1% [95% confidence interval (CI) 23.0–25.3%]. Among 7385 HCWs, the seroprevalence of anti-S1-RBD IgG antibodies was 25.6% (95% CI 23.5–27.8%). Conclusions: Nearly one in four individuals aged ≥10 years from the general population as well as HCWs in India had been exposed to SARS-CoV-2 by December 2020.